2005
DOI: 10.1002/art.21026
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X chromosome inactivation in blood cells of women with scleroderma

Abstract: Objective. Scleroderma (SSc) is an autoimmune disease of unknown etiology. The disease is 3-8 times more frequent in women than in men. The role of X chromosome inactivation (XCI) in the predisposition of women to autoimmunity has been questioned. Until now this has not been illustrated experimentally. This study was undertaken to test the hypothesis that disturbances in XCI mosaicism may be involved in the pathogenesis of the disease in female patients with SSc.Methods. Seventy female SSc patients and 160 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 33 publications
4
128
3
2
Order By: Relevance
“…Of these females, approximately 18% displayed extreme skewing (>90:10). This result is consistent with our previous study, ( 12 ) and indicates that skewed X-inactivation could be a common finding in different population groups.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Of these females, approximately 18% displayed extreme skewing (>90:10). This result is consistent with our previous study, ( 12 ) and indicates that skewed X-inactivation could be a common finding in different population groups.…”
Section: Discussionsupporting
confidence: 94%
“…Clinical characteristics of the patients and controls have been published elsewhere. ( 12,13 ) The ethics review boards at the participating institutions approved the study protocol. Informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have suggested that women affected with specific female-preponderant autoimmune diseases, i.e., scleroderma, manifest a skewed XCI pattern in their peripheral white blood cells. 25 In PBC, however, we failed to demonstrate such preferential inactivation. 21 …”
Section: Introductioncontrasting
confidence: 61%
“…The explanation is often that they have skewed X chromosome inactivation (8). Recent research has shown a higher prevalence of skewed X chromosome inactivation in some autoimmune diseases; this was first found for systemic sclerosis (10). Skewed X chromosome inactivation has been found in autoimmune thyroid disease, both Hashimoto's thyroiditis and Grave's disease (11) and in rheumatoid arthritis (12), but not in primary Sjögren's syndrome, systemic lupus erythematosus, primary biliary cirrhosis or multiple sclerosis (2, 13, 14) ( Table 1).…”
Section: Skewed X Chromosome Inactivation and Autoimmunitymentioning
confidence: 99%